Role of Sphacelotheca sorghii adapted to Ischaemum ciliare and sugarcane on whip smut occurrence in sugarcane - P. NALLATHAMBI; D. MOHANRAJ, R. VISWANATHAN, P. PADMANABAN (Indian Phytopathology, 2002)
The causal organism of ovaricolous smut on I. ciliare in Kerala, India, was isolated and identified as S. sorghii. Teliospores of S. sorghii were compared with teliospores of Ustilago scitaminea from sugarcane and symptoms caused by the 2 fungi were compared.